Juridical Review of Civilians Wearing Rfs Car Plates Reviewed by Law Number 22 Years 2009 on Traffic and Road Transport - Ahmad Zulfa Rangkuti; Abdul Hakim; Maya Jannah (International Journal Labs, 2023)
This study aims to find out and analyze the regulations regarding the manufacture of